The Effectiveness of Gold Pawn Auctions in Resolving Default on Rahn Financing: A Sharia Compliance Analysis at Pegadaian Syariah UPS Ajibarang - Anggita Isty Intansari; Sulasih; Azka Nur Diana; Amanah Aida Qur'an (Wealth: Journal of Islamic Banking and Finance, 2026)
Default on rahn financing poses a challenge for Pegadaian Syariah because it risks causing losses. Gold pawn auctions are the main strategy to resolve customers who fail to pay on time. The research uses a descriptive qualitative method. Data were collected thru in-depth interviews, observations, and documentation from 5 informants consisting of managers, auction officers, and defaulting customers. The research results show that the gold pawn auction is conducted in a structured and effective manner. The process begins with issuing a warning to the defaulting customer, followed by the formation of the auction implementation team. The auction is conducted fairly, transparently, and responsibly, reflecting the application of sharia compliance principles. Transparency efforts are realized thru the delivery of gold value estimates to customers before the auction via WhatsApp groups and announcement boards at CPS Pasar Wage. The determination of the auction price refers to the current estimated gold price, and the auction results are directly communicated to the customers along with any remaining funds, if applicable. In conclusion, the gold pawn auction strategy at Pegadaian Syariah UPS Ajibarang is effective in addressing default on rahn and is in accordance with sharia compliance principles. These findings have implications for strengthening the governance of sharia-based microfinance grounded in transparency and justice.